THE UTILIZATION OF FOLKLORES AND THE HAPPY STRATEGY TO IMPROVE ENGLISH SPEAKING SKILL AND SELF CONCEPT (BEST PRACTICES FOR NONFORMAL EDUCATION) - Wiwiek Afifah (UAD TEFL International Conference)
This paper aims to discuss: (1) the integration of moral values through folklore in narrative texts, (2) the implementation of the happy strategy in teaching and learning processes, and (3) the improvement of speaking skill and self concept. The integration of moral values in folklores as narrative texts can be done to fulfil the learning targets. It is because students will be supported to internalize and actualize those values in their life. Some moral values that can be stressed in the integration of folklores are how to be an honest one, confident, careful, communicative, and down to earth person. The Happy strategies are joyful learning activities that can support students in learning how to speak effectively. It is because learning experiences on how to speak and to communicate were framed fun and relax. The characteristic of the happy strategies included ice breaking, storytelling, role playing, self assessment, peer assessment, and selected report. The strategy also made students felt directly aware of their performance from the result of peer assessment. The teaching strategy that had been implemented in non formal education especially for packet B program was proven to be appropriated. Having been implemented the language input (moral values based on folklores) and the happy strategies, student’s linguistic competence, linguistics performance (speaking skill) were improved. Furthermore, student’s self concept also changed to be better. It is because they can learn some moral values from the folklores and strengthen them through the reflection session of the class.